From the London Olympics to Brexit to COVID-19: Behind the scenes of British politics: Book Review: Boris Johnson: Unleashed. William Collins, London, 2024. - Varga, Tímea (POLARITIES, 2025)
Boris Johnson was born in New York, United States, in 1964, but his entire political career was spent in the United Kingdom. As a member of the Conservative Party, he served as a Member of Parliament in the House of Commons for London from 2001 to 2008 and again from 2015 to 2023. Between 2008 and 2016, he was elected Mayor of London twice, during which time he was, among other things, responsible for overseeing the organization of the 2012 London Olympic Games. From 2016 to 2018 he held the position of Foreign Secretary, and from 2019 until his resignation in September 2022 he served as Prime Minister of the United Kingdom. Alongside his political career, he also worked as a journalist, editor, and author; among his many published works, the best known is The Churchill Factor, a book about the former British prime minister. After Churchill, Johnson now writes about his own work, political career, and above all the most important foreign and domestic political events of the past 15 years in a substantial memoir. Although the volume clearly falls short of expectations regarding Brexit and should be approached with a large dose of criticism, overall it can be said that its readable, light style offers a great deal to learn about how British politics functions and provides insight into the background of numerous global political events that have taken place over the past 10–15 years.